Estimating Commodity Substitution Bias in the Irish Inflation Rate Statistics during the Financial Crisis - Bermingham, Colin; Coates, Dermot; O'Brien, Derry (Economic & Social Studies, 2016)
Measures such as the Consumer Price Index are important economic indicators setting out price changes in the Irish economy over time. Such measures, however, are subject to various types of measurement bias. The latter can include Commodity Substitution Bias whereby the weights assigned to each item in a representative basket of goods and services cease to fully reflect consumer expenditure patterns over time, and particularly during a period of economic upheaval. This, in turn, can lead to the overstatement (or understatement) of inflation. The Central Statistics Office (CSO) now updates the relevant weights every year, thereby reducing the impact of this bias. In this article, we have endeavoured to estimate the size of the bias in the period leading up to the introduction of the new methodology in 2012. The results presented here indicate that the rate of inflation was slightly understated. The degree of this measurement bias was not significantly higher than that identified in other countries in which this phenomenon has been examined, albeit that in the latter countries an upward bias (or overstatement) was found.